A new species of Oroplexia (Lepidoptera: Noctuidae) from China - Gyulai, Peter; Saldaitis, Aidas (Zootaxa, 2015)
The genus Oroplexia Hampson, 1908 comprises some 25 known species. Oroplexia is a south Asiatic, widely distributed genus, displays the highest diversity from the monsoon influenced regions of the Central and Southern Himalaya (Nepal, Myanmar and Vietnam) and Southern China (Sichuan and Yunnan provinces) to India (Hindostan) to the South.